Bioactive compounds and antimalarial potential of sponge Aaptos suberitoides - Wahyuni E. Nanda, Kasta Gurning, Respati Tri Swasono, Winarto Haryadi (Journal of Applied Pharmaceutical Science, 2025)
Indonesia has abundant marine biota that can be used for various pharmacological activities. Among these, the sponge Aaptos suberitoides (A. suberitoides), which is rich in alkaloid compounds, and this group is reported to show antiplasmodium activity. This research aims to identify alkaloid compounds using Liquid Chromatography-High Resolution Mass Spectrometry (LC-HRMS) and test their antimalarial activity in vitro and molecular docking. Extraction was done using the mixture of dichloromethane (DCM) and methanol (1:1). The DCM phase extraction was followed by gradual partitioning with ethyl acetate and water. Phytochemical screening was performed on the dried extracts. The ethyl acetate extract was purified using column chromatography. The purified fractions were tested in vitro for antimalarial activity, and the most active fraction was subjected to compound identification using LC-HRMS as well as molecular docking studies on the 1J3K and 1J3J proteins. The results of the phytochemical screening of the ethyl acetate extract showed that it contained alkaloids with an IC50 value of 0.8189 μg/ml. Fraction number 12 resulting from the purification of ethyl acetate extract has the most potential as an antimalarial, with IC50 values of 00.423± 0.243 μg/ml and 10.21 ± 3.63 μg/ml, in the heme polymerization and antipalsmodium methods, respectively). Compounds identified in the most potent fraction were konbamidin, demethylaaptamine, penicyclone D, and two compounds with codes NP-011220 and NP-013736, which are thought to be new compounds. The results of studies using a molecular docking approach show that demethylaaptamine and penicyclone D are active against malaria proteins coded 1J3K and code 1J3J, respectively. Bioactive compounds from the sponge A. suberitoides can be developed into potential active ingredients for the treatment of malaria from natural marine biota.
Keywords: Alkaloids, marine sponges, A. suberitoides, antimalarial, antiplasmodial